Assessing the reliability and educational value of YouTube videos on computer-controlled local anesthesia in dentistry. - Hulya Cerci Akcay; Erdal Cem Kargu; Nefise Seker (PLoS ONE)
Objective This study aimed to assess the scientific accuracy, content quality, and educational value of YouTube™ videos related to computer-controlled local anesthesia (CCLA) techniques in dentistry. Materials and methods A total of 100 videos were screened using predefined keywords, and 48 met the inclusion criteria. Videos were assessed using the Global Quality Scale (GQS), DISCERN tool, JAMA benchmark criteria, and the Video Information and Quality Index (VIQI). Scientific content was scored using a structured rubric across six domains. Interobserver reliability was evaluated using Weighted Kappa and Intraclass Correlation Coefficient (ICC). Confidence intervals were calculated for key metrics. Group comparisons were performed using the Mann-Whitney U test, and correlations were analyzed using Spearman's rho (p < 0.05). Results Videos from academic sources had significantly higher scores across all quality and reliability indicators. The mean GQS was 2.6 (95% CI: 2.3-2.9), DISCERN 11.7 (95% CI: 10.8-12.6), JAMA 1.8 (95% CI: 1.7-1.9), and VIQI 12.5 (95% CI: 11.7-13.3). Strong positive correlations were found between DISCERN and VIQI (r = 0.809), and between total content score and both DISCERN (r = 0.803) and VIQI (r = 0.655). Conclusion Although YouTube™ provides accessible information on CCLA, many videos lack scientific rigor and educational depth. Content produced by academic institutions is significantly more reliable. Dental educators are encouraged to integrate high-quality video content into curricula to improve media literacy and student learning outcomes.